2020
DOI: 10.1177/0269215520975327
|View full text |Cite
|
Sign up to set email alerts
|

ZMILE, a multicomponent self-management intervention for adults with epilepsy: Rationale and description of the intervention

Abstract: Objective: In this paper, we aim to provide a comprehensive description of the multicomponent self-management intervention for adults with epilepsy, ZMILE. Rationale or theory: Acquiring self-management skills has been shown to play a vital role in enabling patients with epilepsy overcoming (health-related) struggles in daily life and coping with limitations their condition poses on them. ZMILE is a course consisting of education (to increase concordance to treatment), goal-setting (proactive coping), and self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Moreover 6) revealed that there was a highly significant relation between level of patient education and their knowledge regarding epilepsy management and self-care behavior. Table (7) showed that there was a positive strong relation between patient knowledge regarding epilepsy management and patient epilepsy knowledge as measured by EKS (r= 0.548), a positive strong relation between patient knowledge and self-care behavior as measured by ESMS (r=0.611) and a positive strong relation between patient epilepsy knowledge and their self-care behavior (r=0.625) at P ≤ 0.001.…”
Section: Table (3)mentioning
confidence: 98%
“…Moreover 6) revealed that there was a highly significant relation between level of patient education and their knowledge regarding epilepsy management and self-care behavior. Table (7) showed that there was a positive strong relation between patient knowledge regarding epilepsy management and patient epilepsy knowledge as measured by EKS (r= 0.548), a positive strong relation between patient knowledge and self-care behavior as measured by ESMS (r=0.611) and a positive strong relation between patient epilepsy knowledge and their self-care behavior (r=0.625) at P ≤ 0.001.…”
Section: Table (3)mentioning
confidence: 98%
“…Boosting motivation entails empowering the patient and emphasizing the advantages associated with behavior change. Behavior skills involve imparting practical skills and strategies to the patients to expedite behavior change[ 9 , 10 ]. As an all-encompassing framework, the IMB model presents a targeted strategy for health education styled to the needs of unilateral vestibular dysfunction (UVH) patients.…”
Section: Integrating the Imb Model In Vestibular Dysfunction Carementioning
confidence: 99%